Engineered Wood with Hierarchically Tunable Microchannels toward Efficient Solar Vapor Generation - Cui, Tongtong (Langmuir : the ACS journal of surfaces and colloids, 2022)
Wood-based solar steam evaporators have been attracting increasing interest due to their great potential for addressing water scarcity by utilizing sustainable materials and energy. However, engineering a 3D porous structure within the wood lumens and its effect on solar vapor evaporation have not yet been well explored. Here, a natural wood-based solar evaporator with hierarchical pores is fabricated by assembling polyvinyl alcohol within the lumens through an ice-templating approach. The polyvinyl alcohol porous network is engineered from vertically aligned microchannels to dendritically bridged pores with a narrowed size of a few micrometers and significantly increased surface area. Although the formation of plenty of microscopic channels increases the capillary force in comparison to the native wood lumen, the morphology change induces a high tortuosity factor of the porous structure, resulting in a reduced water transportation rate as well as an increased contact angle. On the other hand, the high surface area of the engineered wood lumens and the good hydrophilicity of the filled polyvinyl alcohol improve the ratio of the formed intermediate water, contributing to reduced vaporization enthalpy. Consequently, by using polydopamine as the photothermal material, the hierarchically structured polyvinyl alcohol-wood solar evaporator exhibits an evaporation rate of 1.6 kg m-2 h-1 under 1 sun irradiation and a high solar evaporation efficiency of up to 107%, which are higher than most of the reported natural-wood-based solar evaporators. Moreover, by exploring the correlation between porous morphology and performance, it has been found that the polyvinyl alcohol-wood composite not only presents an inexpensive and sustainable evaporator but also provides guidelines for designing high-performance steam generation devices